AN ANALYSIS OF TEACHERS’ STRATEGIES IN TEACHING ENGLISH SPEAKING SKILL AT SMA NEGERI 1 BUNGO - Duriyah duriyah (Universitas Muhammadiyah Muara Bungo, 2022)
The objective of this research was to describe about the teachers strategies in teaching English speaking skill at SMA N 1. Speaking is needed for the student to convey their goal and to make them fluent in speaking. To achieve the goal of the lesson, the teacher needs the good and interesting strategies to make the student easier to understand about the material. To gain the needed data, the researcher used observation sheet and interview guideline based on three expert theories. They are killian (1999), Leo (2013). And Anjaniputra (2013). Observation sheet was to identify the strategies that is used by the teacher and interview guideline was to collect the data about the teachers’ reason of choosing that strategies. This research was conducted descriptive qualitative research with phenomenal approach. Descriptive qualitative research with phenomenal method was to describe about the teachers experience in teaching English speaking skill at SMA N 1 Bungo. for the participants, there were 4 English teachers at SMA N 1 Bungo. The results showed that the teachers used 9 strategies in teaching English speaking skill. There were plenty of practice, telling and showing, questioning for checking understanding, setting clear lesson and goals it, teach strategies not just content, getting student working together, training interview, improving their discussion, and make your idea.in addition, plenty of practice become the strategy mostly used by the teacher because speaking need practice to increae the student speaking skill. Keyword: Speaking, Teacher, Teachers’ Strategies